LATE DYSFUNCTION OF THE GRAFTED KIDNEY: CAUSES, MORPHOLOGICAL STRUCTURE, PROPHYLAXIS AND TREATMENT - E. S. Stolyarevich; N. A. Tomilina (Вестник трансплантологии и искусственных органов)
The most important causes of late renal graft dysfunction (late acute rejection, chronic rejection, chronic neph- rotoxicity induced by calcineurin inhibitors (CNI) and nonspecific nephrosclerosis), their morphological charac- teristics and the current approaches to their treatment are considered. One of the ways to influence the prevention and the course of late acute rejection which is under discussion in literature is the conversion from cyclosporine A to tacrolimus. The switch from standart to low dosage cyclosporine in combination with proliferative signal in- hibitors (sirolimus, everolimus) is considered as a way to prevent the progression of nephrosclerosis due to CNI- nephrotoxicity. In cases where the main cause of the late kidney graft dysfunction is nonspecific nephrosclerosis the treatment with ACE-inhibitors and optimization with CNI-dosage may be recommended.